2012
DOI: 10.1111/eci.12024
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of BRD7 expression in colorectal carcinoma

Abstract: BRD7 may serve as a potential prognostic biomarker of human colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Accumulating evidence demonstrates that inactivation of the BRD7 gene contributes to the development of many human cancers by transcriptional dysregulation [1,2,[6][7][8][9][10][11][12][13]. BRD7 regulates signaling pathways that involve cell growth, apoptosis, cell cycle, and mobility [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence demonstrates that inactivation of the BRD7 gene contributes to the development of many human cancers by transcriptional dysregulation [1,2,[6][7][8][9][10][11][12][13]. BRD7 regulates signaling pathways that involve cell growth, apoptosis, cell cycle, and mobility [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that BRD7 was also down-regulated in multiple types of human cancer, including breast [6], prostate [7], endometrial [8], colorectal [9], ovarian [10], and pancreas cancer [11], glioma [12], and osteosarcoma [13]. BRD7 can inhibit cell growth through multiple mechanisms, including cell cycle arrest and apoptosis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that BRD7 was mostly located in the nucleus and regulated chromatin remodeling[1517]. More importantly, increasing evidences showed that BRD7 were downregulated in many cancers such as epithelial ovarian carcinoma, breast cancer, nasopharyngeal cancer and colorectal carcinoma [1821]. For example, Hu et al showed that BRD7 acted as a tumor suppressor in osteosarcoma, and knockdown of BRD7 increased colony formation, tumor growth and cell proliferation of osteosarcoma[22].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure was described previously [30, 35, 37]. Immunohistochemical analysis was performed on prepared3-μm sections.…”
Section: Methodsmentioning
confidence: 99%